Inclusive Leadership and Workplace Happiness: Thriving as Mediator and Workaholism as Moderator in Indonesia - Reni Rosari; Amin Wibowo; Claudius Budi Santoso; Tur Nastiti; Heni Ardianto; Vania Olivine Danarilia (SAGE Open, 2025)
With the growing recognition of inclusive leadership in organizational practices, understanding its influence on employee happiness has become increasingly important. This study examines the relationships among inclusive leadership, thriving at work, workplace happiness, and workaholism within Indonesian state-owned enterprises. In 2024, we surveyed 413 employees from various state-owned Indonesian companies. Participants completed scales measuring inclusive leadership, thriving at work, workplace happiness, and workaholism. Data were analyzed using the SPSS PROCESS macro program, specifically Model 7, to test the moderated mediation hypotheses. The results demonstrate that inclusive leadership positively influences workplace happiness and thriving. Additionally, thriving at work mediated the relationship between inclusive leadership and workplace happiness. Interestingly, workaholism positively moderated this mediated relationship, indicating that employees with higher workaholic tendencies experienced greater happiness when thriving at work. Organizations should, therefore, emphasize inclusive leadership practices that promote personal growth, particularly in cultures valuing high performance and dedication, such as Indonesia. For future research, comparative analyses involving different cultures and industries are recommended to deepen our understanding of these dynamics globally.